Public Understanding of Trafficking in Human Beings in Great Britain, Hungary and Ukraine - Sharapov, Kiril (Anti-Trafficking Review, 2019)
This article provides a summary of research undertaken to investigate public awareness and understanding of human trafficking in Great Britain, Hungary and Ukraine. Responding to the lack of reliable empirical data on this issue, the research relies on representative national opinion surveys to assess the extent of public awareness of what constitutes human trafficking, the sources of knowledge underpinning this awareness, and respondents’ attitudes towards key dimensions of human trafficking as embedded in international and respective national legal and policy frameworks and discourses. Conceptually, this article reinforces recent calls for policy and media paradigm shifts from understanding human trafficking as a phenomenon of crime and victimhood, to, above all, a human rights concern linked to the broader issues of sustainable development and social justice. Methodologically, the study highlights the role of opinion surveys as a measure of effectiveness and impact of anti-trafficking awareness campaigns. In practical terms, the article presents a set of data which can be useful for policy-makers, anti-trafficking activists, and national media in designing impactful awareness-raising campaigns and interventions.